Basic Research in Manufacturing and its Contribution to an Eco-friendly Application of Cold Forging - Engel, Ulf (IMechE Conference Transactions-Forging and Related Technology (International Conference ICFT'98), 1998)
Basic research in manufacturing is located between the extremes of pure basic research and industrial R&D, the impulses of which are the better understanding of process mechanisms on the one hand, and mainly economical interests on the other. Due to this intermediate position, basic research combines some characteristic features of both extremes with the special advantage to be more independent of the compulsions given by the driving forces described above. That is the chance to contribute to the ecological objective in a more forward looking way exceeding distinctly in particular the actual legal obligations.
LFT Import::2019-08-05 (1370)